2019
DOI: 10.3389/fncel.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Increases Phasic and Tonic GABAergic Transmission in CA1 Region of Mouse Hippocampus

Abstract: Oxytocin is a neuropeptide that plays important peripheral and central neuromodulatory functions. Our data show that, following activation of oxytocin receptors (OtRs) with the selective agonist TGOT (Thr 4 ,Gly 7 -oxytocin), a significant increase in frequency and amplitude of spontaneous inhibitory postsynaptic currents (sIPSC) occurred in hippocampal CA1 pyramidal neurons (PYR) in mice. TGOT affected also sIPSC deactivation kinetics, suggesting the involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…2018), but up‐modulates L‐type Ca 2+ channels to excite CA1 GABAergic interneurons (Maniezzi et al . 2019). In ventral tegmental area and interfascicular nucleus of mouse midbrain, OXT increases neuronal excitability by activating a non‐selective cation channel and Na + –Ca 2+ exchanger (Tang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018), but up‐modulates L‐type Ca 2+ channels to excite CA1 GABAergic interneurons (Maniezzi et al . 2019). In ventral tegmental area and interfascicular nucleus of mouse midbrain, OXT increases neuronal excitability by activating a non‐selective cation channel and Na + –Ca 2+ exchanger (Tang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of OXTRs has been shown to increase neuronal excitability by distinct ionic mechanisms depending on neuronal types. In the hippocampus, activation of OXTRs inhibits KCNQ-based M channels to depolarize CA2 pyramidal neurons (Tirko et al 2018), but up-modulates L-type Ca 2+ channels to excite CA1 GABAergic interneurons (Maniezzi et al 2019). In ventral tegmental area and interfascicular nucleus of mouse midbrain, OXT increases neuronal excitability by activating a non-selective cation channel and Na + -Ca 2+ exchanger (Tang et al 2014).…”
Section: Ionic Mechanisms Underlying Oxtr-mediated Excitation Of Cel mentioning
confidence: 99%
“…We also have found that IN and less IP administered OXT improved short term memory in the Y maze, and that was correlated with a decline of oxidative stress status. OXT receptors are distributed abundantly in hippocampus and other brain regions involved in memory functions, suggesting OXT role in memory formation [ 74 ] and activation of hippocampal OXT receptors was showed to favor synaptic plasticity and transmission and suppressing neuronal background firing [ 75 , 76 , 77 ]. Several animals studies using IN OXT treatment in rodents with impaired hippocampal functioning or impaired memory have reported also positive effects [ 50 , 75 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide can also act presynaptically to affect neurotransmitter secretion (Dölen et al, 2013 ; Bakos et al, 2018 ). Overall, from a physiological perspective, oxytocin influences cell viability, synaptic and structural plasticity in neurons (Bakos et al, 2018 ; Jurek and Neumann, 2018 ; Pekarek et al, 2020 ), and modulates the balance of excitatory and inhibitory activity in regions such as the cerebral cortex and hippocampus (e.g., Mitre et al, 2016 ; Grinevich and Stoop, 2018 ; Lin and Hsu, 2018 ; Lopatina et al, 2018 ; Tirko et al, 2018 ; Cilz et al, 2019 ; Maniezzi et al, 2019 ; Tan et al, 2019 ), amygdala (Crane et al, 2020 ), and nucleus accumbens (Moaddab et al, 2015 ; Cox et al, 2017 ). Rodents lacking oxytocin or OXTR display impaired sociability and social memory (Ferguson et al, 2000 ).…”
Section: The Neuroscience Of Oxytocin—animal Studiesmentioning
confidence: 99%